1993
DOI: 10.1073/pnas.90.22.10413
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and magnetoencephalographic correlates of plasticity in the adult human brain

Abstract: Recent behavioral and physiological evidence suggests that even brief sensory deprivation can lead to the rapid emergence of new and functionally effective neural connections in the adult human brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
2
10

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(136 citation statements)
references
References 41 publications
9
112
2
10
Order By: Relevance
“…This discovery suggests that the peripheral and central sensory pathways endured and remained viable after prolonged periods of postamputation disuse, which is compelling in light of evidence suggesting that although the subcortical topography of the limb afferents is maintained after amputation, spinal cord and brainstem afferents from adjacent residual limb and face sprout into and strongly reactivate territory once occupied by the missing limb (7-10). Interestingly, although both patients examined in this work report the presence of a phantom limb, neither patient has ever felt any evoked phantom-limb sensations elicited from tactile stimulation of the face or trunk (11)(12)(13). The reactivation of sensation generated relatively extensive evoked sensations of the missing limb in both patients.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery suggests that the peripheral and central sensory pathways endured and remained viable after prolonged periods of postamputation disuse, which is compelling in light of evidence suggesting that although the subcortical topography of the limb afferents is maintained after amputation, spinal cord and brainstem afferents from adjacent residual limb and face sprout into and strongly reactivate territory once occupied by the missing limb (7-10). Interestingly, although both patients examined in this work report the presence of a phantom limb, neither patient has ever felt any evoked phantom-limb sensations elicited from tactile stimulation of the face or trunk (11)(12)(13). The reactivation of sensation generated relatively extensive evoked sensations of the missing limb in both patients.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that cortex has far more representational plasticity than previously believed. Indeed, recent studies have shown that cortex retains representational plasticity into adulthood (e.g., radical "remapping" of somatosensory cortex after amputation, in humans and in infrahuman primates-Merzenich, Recanzoni, Jenkins, Allard, & Nudo, 1988;Pons et al, 1991;Ramachandran, 1993; see also Greenough, Black, & Wallace, 1993;Greenough, McDonald, Parnisari, & Camel, 1986). Although one cannot entirely rule out the possibility that neurons are born "knowing" what kinds of representations they are destined to take on, the case for innate representations does not look very good right now.…”
Section: "It Is a Certain Wiring Of The Microcircuitry That Is Essentmentioning
confidence: 99%
“…These changes have been associated with phantom phenomena, especially pain (Flor et al, 1995;Flor, 2002), implying that nonpainful phantom phenomena might not be associated with somatomotor plasticity , Lotze et al, 2001. Nevertheless, although phantom pain is seldom directly tested, and some authors deal with plasticity without pain (Giraux et al, 2001;Vargas et al, 2009), most focus on upper limb amputees who report phan-tom pain (Ramachandran, 1993;Flor et al, 1998;Lotze et al, 1999Lotze et al, , 2001MacIver et al, 2008).…”
Section: Introductionmentioning
confidence: 99%